Investigating the Realization of Speech Function in a Speech through Systemic Functional Linguistics Perspective - Herman Herman; Ridwin Purba; Putri Anggita Sijabat; Nanda Saputra; Nguyen Van Thao; Mas’ud Muhammadiah (Script Journal: Journal of Linguistics and English Teaching, 2022)
This research aims to classify the type of Speech function process. This research employed systemic functional linguistics theory of Halliday, particularly speech function as a tool of analysis, more specific this research analyzed process of speech function. The phenomenon of speech function, in communicating people need other people who will be our listeners as well as our talking partners at the same time. These actions give rise to various different phenomena due to variations in the ability of each person to apply language and linguistics as well as their cultural background. Because of these divergences, it is undeniable that misunderstandings between listeners and speakers often occur, especially when both participants in a communication are non-native speakers. The data collected from President Joseph Robinette Biden Jr. speech at United State of America from white House You-Tube on March 11th 2021. The researchers used qualitative research design to answer the research question and choose content analysis because the result of the data analyzed is in descriptive phenomenon such as word, clause and utterance. The researchers used documentation as the research instrument. The researchers collected the data that is posted on March, 11th 2021. The findings of this research showed 294 Data that Statement is 292data (99%), Question find 2(1%) data, 0 data for command and offer. The most type of speech function is Statement. In contrast which just 2 question and nothing data for command and offer in his speech